Local-global geographies of tacit knowledge production in London and New York's advertising and law professional service firms - James R. Faulconbridge (2005)
For economic geographers interest in the role of knowledge in economic activities and a ‘knowledge economy’ raises questions about how geography enables (and disables) learning and whether the production of tacit knowledge has exclusively local or multiple overlapping geographies. This thesis engages with this debate and considers its relevance to the geographies of tacit knowledge production (learning) in the employees of global advertising and law professional service firms operating in London and New York City. It begins by critically engaging with theories of knowledge, learning and their geographies to develop a spatially sensitive approach to examine learning. Such an analysis is then applied in order to understand the geographies of knowledge production in global advertising and law firms. Three themes are addressed. First, why is tacit knowledge important in the work of these firms? Second, what are the key practices involved in producing such knowledge? Third, what are the geographies of these practices and how important is the local scale (the communities within London and New York) and the global scale (the communities stretched between offices of the global firms studied) for knowledge production. Research findings from semistructured interviews highlight the multiple geographies of learning in the firms studied at both local and global scales. This is enabled by a number of ‘embedding’ forces that ‘smooth’ the learning process and that have multiple geographies themselves. It is therefore argued that a relational and topological analysis that traces the learning networks across space most usefully provides insights into the geographies of knowledge production. This reveals that the ‘networks and spaces of learning’ are fluid and transcend spatial scales when suitable constructed.